Strategi Perubahan Budaya Organisasi dalam Meningkatkan Kecerdasan Emosional dan Spiritual Personal - Muhammad Rahman (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2022)
This study aims to determine the strategy of organizational culture change to increase emotional and spiritual intelligence in organizational members. The method used is a qualitative approach with the type of library research (library research). Organizational culture change strategies include; aggressive approach, peaceful approach, corrosive approach and indoctrination approach. Then there are five stages of change, namely; deformative, reconciliative, acculturative, enactive and formative. Furthermore, the dimensions of change include; structural dimension, space and time dimension, change process dimension, contextual dimension and subjective dimension. The parameters are; expressive power, communality power, penetration power, adaptive power and endurance. Organizations that expect their organization's existence to be maintained must of course be friends with change. Organizational culture will certainly have an effect on organizational members, in this case it is hoped that the changes in organizational culture that are carried out can certainly be one of the foundations in increasing emotional and spiritual intelligence for every individual in the organization. The conclusion is that making a change to the organizational culture in order to improve the emotional and spiritual intelligence of members of the organization of course requires various strategies which must be adapted to each situation so that the desired results can be achieved.